POLA PENGAMBILAN KEPUTUSAN DALAM USAHATANI JAGUNG HIBRIDA (Zea mays L) DI NAGARI LUBUK GADANG TENGGARA KECAMATAN SANGIR KABUPATEN SOLOK SELATAN - Yeni, Sri Afri; Gusriati; Herda Gusvita (Jurnal Research Ilmu Pertanian, 2021)
The purpose of this study was to analyze hybrid maize farming and study the pattern of decision making in hybrid maize farming in Nagari Lubuk Gadang Tenggara, Sangir District, South Solok Regency. This research was conducted in Nagari Lubuk Gadang Tenggara from April to May 2019. The research method used was descriptive method and survey technique with a population of 58 people from 237 farmers. Samples were taken by census. Data analysis used descriptive quantitative and qualitative, hybrid corn farming analysis and decision making pattern analysis in hybrid corn farming. The results showed that the production of hybrid maize in Nagari Lubuk Gadang Tenggara, Sangir District, South Solok Regency per planting season was 2.909.56 Kg / Ha, the revenue of Rp. 12,220,152.00 / Ha, income of Rp. 8,387,873.30 / Ha, the total cost of Rp. 4,252,585.91 / Ha, and a profit of Rp. 7,967,657.31 / ha, and the R / C ratio is 2.9. The most pattern of decision making in hybrid corn farming is pattern I (the decision is made by the husband alone without involving his wife).